The Effect of Training Using Rubber Media and Leg Dumbbells to Improve Uchi-Mata Ability in Judo Athletes - Ikhwan Anzis; Nurman Ramadhan; Hilmy Aliriad (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study aims to determine the effect of training using rubber and leg dumbbells on improving the uchi-mata technique ability of beginner judo athletes at the Al-Jabbar Dojo, Tuban Regency. The research method used was an experiment with a one-group pretest-posttest design through a quantitative approach. The population and sample in this study amounted to 10 athletes who were selected using a saturated sampling technique. The data collection instrument was carried out through a uchi-mata technique ability test before and after treatment for 14 meetings. Data analysis used the Shapiro-Wilk normality test, Levene's homogeneity test, and the Paired Sample T-Test with the help of SPSS version 23 software. The results of the study showed a significant increase in scores, where the average (mean) pretest score of 47 increased to 79 in the posttest. The results of the hypothesis test proved that the use of resistance media has a positive effect on leg muscle strength, balance, and coordination of athletes. The conclusion of this study is that training using rubber and leg dumbbells is effective in improving uchi-mata technique ability, so it is recommended as an alternative training method for coaches in developing the performance of beginner athletes.